Peroxiredoxin 6 Regulates Glutathione Peroxidase 1-Medited Glutamine Synthase Preservation in the Hippocampus of Chronic Epilepsy Rats - Ji-Eun Kim; Hana Park; Tae-Cheon Kang (MDPI AG, 2023)
Clasmatodendrosis (an autophagic astroglial degeneration) plays an important role in the regulation of spontaneous seizure duration but not seizure frequency or behavioral seizure severity in chronic epilepsy rats. Recently, it has been reported that N-acetylcysteine (NAC), a precursor to glutathione (GSH), attenuates clasmatodendritic degeneration and shortens spontaneous seizure duration in chronic epilepsy rats, although the underlying mechanisms of its anti-convulsive effects are not fully understood. To elucidate this, the present study was designed to investigate whether NAC affects astroglial glutamine synthase (GS) expression mediated by GSH peroxidase 1 (GPx1) and/or peroxiredoxin 6 (Prdx6) in the epileptic hippocampus. As compared to control animals, GS and GPx1 expressions were upregulated in reactive CA1 astrocytes of chronic epilepsy rats, while their expressions were significantly decreased in clasmatodendritic CA1 astrocytes and reactive astrocytes within the molecular layer of the dentate gyrus. Prdx6 expression was increased in reactive CA1 astrocytes as well as clasmatodendritic CA1 astrocytes. In the molecular layer of the dentate gyrus, Prdx6 expression levels were similar to those in control animals. NAC ameliorated clasmatodendrosis through the increment of GS and GPx1 expressions, while it abolished Prdx6 upregulation. 1-hexadecyl-3-(trifluoroethgl)-sn-glycerol-2 phosphomethanol (MJ33, a selective inhibitor of aiPLA2 activity of Prdx6) alleviated clasmatodendrosis by enhancing GPx1 and GS expressions in clasmatodendritic CA1 astrocytes without changing the Prdx6 level. NAC or MJ33 did not affect GS, GPx1 and Prdx6 expression in astrocytes within the molecular layer of the dentate gyrus. These findings indicate that upregulated aiPLA2 activity of Prdx6 may abolish GPx1-mediated GS preservation and lead to clasmatodendrosis in CA1 astrocytes, which would extend spontaneous seizure duration due to impaired glutamate-glutamine conversion regulated by GS. Therefore, the present data suggest that aiPLA2 activity of Prdx6 in astrocytes may be one of the upstream effectors of seizure duration in the epileptic hippocampus.